Small circular interfering RNAs (sciRNAs) as a potent therapeutic platform for gene-silencing. Issue 18 (11th September 2021) - Jahns, Hartmut; Degaonkar, Rohan; Podbevsek, Peter; Gupta, Swati; Bisbe, Anna; Aluri, Krishna; Szeto, John; Kumar, Pawan; LeBlanc, Sarah; Racie, Tim; Brown, Christopher R; Castoreno, Adam; et al.
Abstract: In order to achieve efficient therapeutic post-transcriptional gene-silencing mediated by the RNA interference (RNAi) pathway, small interfering RNAs (siRNAs) must be chemically modified. Several supra-RNA structures, with the potential to stabilize siRNAs metabolically have been evaluated for their ability to induce gene silencing, but all have limitations or have not been explored in therapeutically relevant contexts. Covalently closed circular RNA transcripts are prevalent in eukaryotes and have potential as biomarkers and disease targets, and circular RNA mimics are being explored for use as therapies. Here we report the synthesis and evaluation of small circular interfering RNAs (sciRNAs). To synthesize sciRNAs, a sense strand functionalized with the trivalent N -acetylgalactosamine (GalNAc) ligand and cyclized using 'click' chemistry was annealed to an antisense strand. This strategy was used for synthesis of small circles, but could also be used for synthesis of larger circular RNA mimics. We evaluated various sciRNA designs in vitro and in vivo . We observed improved metabolic stability of the sense strand upon circularization and off-target effects were eliminated. The 5′-( E )-vinylphosphonate modification of the antisense strand resulted in GalNAc-sciRNAs that are potent in vivo at therapeutically relevant doses. Physicochemical studies and NMR-based structural analysis, together with molecular modeling studies, shed light on the interactions of this novel class of siRNAs, which have a partial duplex character, with the RNAi machinery.